The triple jump. Model technique analysis sheet for the horizontal jumps - Hutt, E. (Modern Athlete & Coach, 2008)
Bewegungsanalyse des Dreisprungs: Anlauf, Absprung, Hop, Step, Jump, Landung. Mit Kriterienkatalog.